Daily behaviour and home range of adult rehabilitant Javan slow loris (Nycticebus javanicus É. Geoffroy, 1812) in Gunung Sawal Nature Reserve, Ciamis, West Java - Dolly Priatna; Aris Hidayat; Yossa Istiadi; Ammy Nurwati; Ahmad Yanuar; Adi Susilo (Universitas Pakuan, 2023)
This study aims to determine the differences in daily behaviour and home range of male and female rehabilitated Javan slow loris (Nycticebus javanicus) in Gunung Sawal Nature Reserve, Ciamis, West Java, Indonesia. The study was conducted on four individuals of Javan slow loris rehabilitates (two adult males and two adult females) during their post-released monitoring period. Those animals were fitted with a radio transmitter and were monitored for their daily behaviour and home range for six months (May - October 2018). The focal animal sampling method was employed for daily behaviour observation. The home range of each individual was estimated by Minimum Convex Polygon (MCP) and Kernel Density Estimation (KDE) methods. Data analysis was descriptively displayed in maps, tables, and figures. According to the statistical analyses of the Mann Whitney U test, there are no significant differences (μ = 1,074,554.5 [p 0.01]; P-Value 0.238 0.01) in the daily behaviour of male and female Javan slow loris rehabilitate. In contrast, the home range (vertically and horizontally) of female and male Javan slow loris rehabilitate are significantly different (μ = 816,286.0 [p 0.01]; P-Value 0.000 0.01). Penelitian ini bertujuan untuk mengetahui perbedaan perilaku harian dan wilayah jelajah kukang jawa (Nycticebus javanicus) jantan dan betina hasil rehabilitasi di Suaka Margasatwa Gunung Sawal, Ciamis, Jawa Barat, Indonesia. Penelitian dilakukan pada empat individu kukang jawa rehabilitan (dua jantan dewasa dan dua betina dewasa) selama masa pemantauan pasca pelepasliaran. Satwa-satwa tersebut dipasangi pemancar radio serta dipantau perilaku harian dan wilayah jelajahnya selama enam bulan (Mei - Oktober 2018). Metode pengambilan sampel